Pengembangan Modul Praktikum Bahasa Inggris - Ni Kadek Nilawati; Gede Wira Bayu; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2023)
Lack of student interest in learning English material. The current learning outcome scores in English courses have decreased. This research aims to create an English practicum module to increase student interest in learning and learning outcomes. This type of research is development. The research model used is the ADDIE development model. The subjects in this research were 6 experts to determine the validity of the module developed. The data collection methods in this research were questionnaires and tests. Data analysis techniques are qualitative descriptive analysis quantitative and inferential statistics. The research results show that the English practicum module obtained a validity index for material experts I and II with an average score of 95.5%, media experts I and II with an average score of 87%, and design experts I and II with an average score of 87. % is included in very good validity. The results of the practical expert assessment obtained a result of 87%. The results of the product effectiveness test stated that the average pretest learning score was 52.79, and the post-test learning results averaged 82.14. The English practicum module could increase student interest in learning and learning outcomes. The results of this research show that the product developed is valid, practical, and effective and is expected to overcome the value of student learning outcomes.